Emergence profile customization technique during implant transfer - Dos Santos, Paulo Henrique [UNESP]; Suzuki, Thais Yumi Umeda; Martini, Ana Paula [UNESP]; De Oliveira Reis, Bruna [UNESP]; Assunção, Wirley Gonçalves [UNESP]; Rocha, Eduardo Passos [UNESP] (Wolters Kluwer, 2019)
This case report aimed to describe the clinical considerations in oral rehabilitation with prostheses on implants in the anterior region, using emergence profile customization technique during implant transfer. A patient presented with a missing left upper central incisor and with not satisfactory esthetic in the other upper incisors. After diagnosis, a treatment plan was elaborated: implant placement in this region; ceramic laminates for teeth 11 and 22, and full crown for tooth 12. During the impression procedure, the implant transfer was customized by copying the gingival profile. The prostheses were made using IPS e.max ceramic system and luted with resin cement. The patient was submitted to annual follow-up examinations that did not show any irregularity or deficiency in the prostheses. The technique performed is a viable alternative that can be used in oral rehabilitation with implants involving anterior teeth because it allows a predictable level of adaptation.
Keywords: Emergence profile; fixed prostheses; oral rehabilitation